Book Review for Petra Bueskens (ed.) Mothering & Psychoanalysis. Clinical, Sociological and Feminist Perspectives - Amanda de Clifford (Psychotherapy and Counselling Journal of Australia)
Between the routines and rituals of mothering I seek out Petra Bueskens’ collection of essays, reaching for its enigmatic cover that features a woman draped in newspaper text, bearing one breast, holding a glass of water in one hand and a leaf in the other, while birds flutter around her shoulders and pencils fire past her.[i] In Mothering & Psychoanalysis Bueskens collects twenty-three essays which together produce a lively dialogue about mothering from psychoanalytic, sociological and feminist perspectives.